A Call for Culturally Responsive Transformational Leadership in College Sport: An Anti-ism Approach for Achieving Equity and Inclusion - Joseph N. Cooper; Ajhanai C. I. Newton; Max Klein; Shannon Jolly (Frontiers in Sociology, 2020)
A longstanding fact in college sports in the United States (U.S.) is the reality that inequities, inequalities, and discrimination have been major issues preventing institutions from fostering harmonious diversity and inclusion. Several reasons for these persistent outcomes include the prevalence of implicit bias, homologous reproduction, hegemonic, and toxic masculinity/patriarchy, colorblind racism, and abstract liberalism to name a few. In addition, multi-level factors (macro-, meso-, and micro-) also influence the existence and salience of negative organizational cultures and climates particularly for groups that are underrepresented and marginalized in society. Despite the fact several leadership styles have been enacted and numerous policy reforms have been adopted over the years, inequities in representation, occupational mobility, position retention, and quality of experiences persist along racial and gender lines. As a result, the purpose of this manuscript is to offer innovative transformational leadership approaches that incorporate anti-racism, anti-sexism, and culturally responsive stances toward achieving true equity and inclusiveness in sport. Using interdisciplinary theories such as the anti-racism framework and culturally responsive leadership, this manuscript presents a paradigm shift for college sport leadership with the intent of cultivating paramount experiences for people across diverse backgrounds.